Korelasi Perilaku Personal Hygiene Remaja Putri Di Sma Budi Mulia Jakarta Pusat Pada Kejadian Keputihan - TAY, JOCELYN; RUSLIM, WELLY HARTONO (Hang Tuah Medical Journal, 2025)
The issue of vaginal discharge among adolescent girls is a significant concern in tropical dan humid countries like Indonesia. Approximately 45% of women in Indonesia experience reccurent vaginal discharge yet, several adolescents still perceive it as a normal condition. This research intends to investigate the connection between hygiene practices and occurrences of vaginal discharge among female students at Budi Mulia Senior High School in Central Jakarta. This analysis adopted a cross-sectional design use an observational approach, involving 146 female respondents, and was conducted from January to February 2025. Data collection utilized a questionnaire and chi-square analysis, revealing that 58,2% maintained excellent personal hygiene, while 50% experienced pathological vaginal discharge. The research indicated a strong link between hygiene practices and vaginal discharge incidence, with a p-value of 0,016.